Object - oriented image analysis methods in disaster risk management : state - of - the - art and prospects for the Philippines :Powerpoint - Kerle, N. (University of Twente, 2020)
This lecture presents: Object-oriented analysis for disaster risk management; Basics of object-oriented analysis; Hazard: Landslide work, Landslide work with LiDAR data; Other risk aspects – Damage mapping; Damage mapping results: Western view example.